Organizational factors, planning capacity, and integration challenges constrain provincial planning processes for nutrition in decentralizing Vietnam - Lapping, Karin; Frongillo, Edward A.; Nguyen, Phuong Hong; Coates, Jennifer; Webb, Patrick; Menon, Purnima (SAGE Publications, 2014)
Translating national policies and guidelines into effective action at the subnational level (e.g., province or region) is a prerequisite for ensuring an impact on nutrition. In several countries, including Vietnam, the focus of this paper, this process is affected by the quality of the decentralized process of planning and action.This study examined how provincial planning processes for nutrition occurred in Vietnam during 2009 and 2010. Key goals were to understand variability in processes across provinces, identify factors that influenced the process, and assess the usefulness of the process for individuals involved in planning and action.A qualitative case-study methodology was used. Data were drawn from interviews with 51 government officials in eight provinces.The study found little variability in the planning process among these eight provinces, probably due to a planning process that was predominantly a fiscal exercise within the confines of a largely centralized structure. Respondents were almost unanimous about the main barriers: a top-down approach to planning, limited human capacity for effective planning at subnational levels, and difficulty in integrating actions from multiple sectors. Provincial-level actors were deeply dissatisfied with the nature of their role in the process.Despite the rhetoric to the contrary, too much power is probably still retained at the central level. A strategic multiyear approach is needed to strengthen the provincial planning process and address many of the key barriers identified in this study.